SKRINING FITOKIMIA DARI INFUSA DAN EKSTRAK ETANOL DAUN LIDAH MERTUA (Sansevieria trifasciata Prain) - Deri Islami; Dedi Kurniawan (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Sansevieria trifasciata prain, known to the public as the tongue-in-law plant, is one of the medicinal plants in Indonesia. Traditionally, this plant, which originates from the tropical African continent, is often used as an antiseptic and antimicrobial. The efficacy of mother-in-law's tongue in curing various diseases is also thought to be related to the chemical compounds it contains, including the leaves and rhizomes of mother-in-law's tongue contain secondary metabolites of the cardenolin group, besides that the leaves also contain flavonoids, tannins and polyphenols. This study aims to determine the phytochemical content of infusion and ethanol extract of mother-in-law's tongue (Santieviera trifasciata prain). This study used two methods, namely multilevel maceration and infusion. This study aims to determine the phytochemical content of infusion and ethanol extract of mother-in-law's tongue (Santieviera trifasciata prain). The results of the phytochemical screening test from the infusion and ethanol extract of Mother-in-law's tongue (Sanseivieria trifasciata prain) leaves contain different chemical compounds, namely the phytochemical screening on the ethanol extract contains alkoloids, flavonoids, terpenoids and tannins compounds. Meanwhile, the infusion phytochemical screening only contained alkoloids and saponin compounds.